SuhB Regulates the Motile-Sessile Switch in Pseudomonas aeruginosa through the Gac/Rsm Pathway and c-di-GMP Signaling - Li, Kewei; Yang, Guangjian; Debru, Alexander B.; Li, Pingping; Zong, Li; Li, Peizhen; Xu, Teng; Wu, Weihui; Jin, Shouguang; Bao, Qiyu (Frontiers in Microbiology, 2017)
Many Pseudomonas aeruginosa virulence traits that contribute to human infections are accepted as being associated with its environmental lifestyle. Therefore, identifying the molecular mechanisms that govern the lifestyle choice is of high significance. We previously reported that a mutation in suhB results in a decrease in swimming motility and increased biofilm formation compared to the wild-type strain. Yet, little is known about how this occurs. In this study, we demonstrated that SuhB inversely regulates motility and biofilm formation through the GacA-RsmY/Z-RsmA cascade. Mutations in gacA or the two small RNAs rsmY/rsmZ, or overproduction of the RsmA protein essentially rescued the motility defect of the suhB mutant. Additionally, we identified a c-di-GMP mediated mechanism for SuhB regulation of motility and biofilm formation. We showed that the ΔsuhB mutant displayed elevated levels of c-di-GMP, and the ΔsuhB motility and biofilm phenotypes could be switched by artificially decreasing c-di-GMP levels. Further experiments led to the identification of the diguanylate cyclase GcbA responsible for regulating the c-di-GMP concentration in ΔsuhB and hence the switch between planktonic and surface-associated growth. Together, our results demonstrate a novel mechanism for SuhB regulation of the lifestyle transition via the Gac/Rsm and c-di-GMP signalling networks in P. aeruginosa.